Concept Mappings: A Contribution to the Teaching and Learning of SDGs - Garrido Gómez, M. Isabel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
As experience has shown, the situation in higher education has changed a lot in recent years and this calls for an unprecedented openness to new forms of teaching and learning. As will be seen, the elaboration of concept maps goes beyond the traditional actions of students and teachers. With the use of this medium, the concepts related to the Sustainable Development Goals are discovered autonomously and the students acquire the meanings to be learned. For this purpose, the use of comparisons is very useful and valuable results can be obtained.